The Increase of Early Childhod’s Motoric Development with Thematic Approach - Sofyan, Hendra (Universitas Negeri Semarang, 2016)
The objective of this research is to increaseearly childhood’s development by using of thematic approach. This action research conducted at Nakkia Kindergarten Group B Jatiwaringin Pondok Gede. This research usedin which 15 childhood of six years old were participated. The development by Kemmis and Tegart which twocycles and each cycle has four steps. They are as follow:(1) plan, (2) action, (3) observe, and (4) reflect. The action research applied to research methods they where qualitative and quantitative research, data analized by using Spradley data analysis model. The research result shows the applying thematic approach wich involved various methods, media and activities increase the development of the children of six years old especialy in motoric development: gross motor and fine motor. Futhermore, the research result can be applied to increase early childhoods development with thematic approach, mainly for learning planning, learning development for teachers, and curricullum in higher education